The role of the multidisciplinary tumor board after endoscopic resection of malignant tumors: is it worth it? - Kouladouros, Konstantinos; Centner, Maximilian; Reißfelder, Christoph; Belle, Sebastian; Kähler, Georg (Surgical endoscopy and other interventional techniques, 2023)
The value of multidisciplinary tumor boards (MTBs) in the treatment of gastrointestinal cancer patients is well known. Most of the current evidence focuses on advanced cancer cases, whereas little is known about the effect of MTBs on early tumors, especially after endoscopic resection. The aim of our study is to evaluate the value of the MTB after endoscopic resection of malignant tumors of the gastrointestinal tract.